Mendelian randomization of circulating polyunsaturated fatty acids and colorectal cancer risk - Khankari, Nikhil K.; Banbury, Barbara L.; Borges, Maria C.; Haycock, Philip; Albanes, Demetrius; Arndt, Volker; Berndt, Sonja I.; Bezieau, Stephane; Brenner, Hermann; Campbell, Peter T.; Casey, Graham; Chan, Andrew T.; et al. (Cancer epidemiology, biomarkers & prevention, 2020)
Background: Results from epidemiologic studies examining polyunsaturated fatty acids (PUFA) and colorectal cancer risk are inconsistent. Mendelian randomization may strengthen causal inference from observational studies. Given their shared metabolic pathway, examining the combined effects of aspirin/NSAID use with PUFAs could help elucidate an association between PUFAs and colorectal cancer risk. Methods: Information was leveraged from genome-wide association studies (GWAS) regarding PUFA-associated SNPs to create weighted genetic scores (wGS) representing genetically predicted circulating blood PUFAs for 11,016 non-Hispanic white colorectal cancer cases and 13,732 controls in the Genetics and Epidemiology of Colorectal Cancer Consortium (GECCO). Associations per SD increase in the wGS were estimated using unconditional logistic regression. Interactions between PUFA wGSs and aspirin/NSAID use on colorectal cancer risk were also examined. Results: Modest colorectal cancer risk reductions were observed per SD increase in circulating linoleic acid [ORLA = 0.96; 95% confidence interval (CI) = 0.93-0.98; P = 5.2 x 10(-4)] and alpha-linolenic acid (ORA(LA) = 0.95; 95% CI = 0.92-0.97; P = 5.4 x 10(-5)), whereas modest increased risks were observed for arachidonic (ORAA = 1.06; 95% CI = 1.03-1.08; P = 3.3 x 10(-5)), eicosapentaenoic (OREPA = 1.04; 95% CI = 1.01-1.07; P = 2.5 x 10(-3)), and docosapentaenoic acids (ORDPA = 1.03; 95% CI = 1.01-1.06; P = 1.2 x 10(-2)). Each of these effects was stronger among aspirin/NSAID nonusers in the stratified analyses. Conclusions: Our study suggests that higher circulating shorter-chain PUFAs (i.e., LA and ALA) were associated with reduced colorectal cancer risk, whereas longer-chain PUFAs (i.e., AA, EPA, and DPA) were associated with an increased colorectal cancer risk. Impact: The interaction of PUFAs with aspirin/NSAID use indicates a shared colorectal cancer inflammatory pathway. Future research should continue to improve PUFA genetic instruments to elucidate the independent effects of PUFAs on colorectal cancer.
Gesehen am 28.07.2020